Development of Hypercontent-Based Learning Materials in Thematic Learning - Nasrulloh, Iman; ., Fitriyani (Fakultas Kewirausahaan Universitas Garut, 2022)
This study aims to develop and implement hypercontent-based learning materials in thematic learning as a response to the challenges of education in the digital era and the Industrial Revolution 4.0. Hypercontent, which integrates various forms of media such as text, images, audio, video, and external links, is designed to provide a more interactive, engaging, and contextual learning experience for students. Using a descriptive approach with the 4-D development model (Define, Design, Develop, and Disseminate), the research emphasizes systematic stages to ensure the quality and validity of the developed materials. The results demonstrate that hypercontent not only enriches thematic learning but also enhances students’ motivation, creativity, and critical thinking. Teachers reported that the use of hypercontent facilitated the delivery of lessons, made content more flexible, and supported independent as well as collaborative learning. However, several challenges remain, including digital literacy gaps among teachers, limited infrastructure, and unequal access to devices and internet connectivity for students. Despite these constraints, the findings underline that hypercontent-based materials can serve as an innovative learning strategy, aligning with the principles of the Merdeka Curriculum and preparing students for global competitiveness. Continuous teacher training, institutional support, and collaboration in content development are crucial for sustaining this innovation.